Virtual Rape In Indonesian Criminal Law: Legal Reality Or Conceptual Challenge? - Sutran, Moh. Raihan Rizaldi (UI Scholars Hub, 2026)
Current technological developments have brought humanity into a new era called the metaverse, a virtual world that allows people to interact through digital avatars. However, this progress has also presented new problems, one of which is virtual rape – rape committed by players through their avatars. Even though there is no direct physical contact, victims can still experience real psychological effects such as trauma, anxiety, and fear. The main problem is there are no regulations in Indonesia that can address this phenomenon yet. Therefore, this article examines the extent to which the phenomenon of “virtual rape” can be considered equivalent to the concept of rape within existing conceptual and legal frameworks. In the absence of such equivalence, it further examines whether virtual rape can nonetheless be classified as a criminal offence, or whether alternative legal frameworks may be applicable to address this phenomenon. The research attempted to answer that question by relying on the comparative studies of United Kingdoms, United States, and European Union. These countries have apparently addressed this issue in many different ways. It is a challenge to argue that virtual rape falls under the rape in the classical languages as rape is considered to be physical sexual assault. Hence it does not fulfil the key elements of rape. However, this does not mean that this issue can be ignored. The virtual world is growing, and the line between the real and digital worlds is becoming increasingly blurred. Sooner or later, the possibility of more serious non-consensual sexual acts in the metaverse remains open or it might be increase to be a bigger problem.